ANALISA WAKTU KERUSAKAN BALOK BETON BERTULANG AKIBAT KOROSI PADA BANGUNAN STRUKTUR DI DAERAH PANTAI - Arie Febry Fardheny (Universitas Lambung Mangkurat, 2005)
Chloride Penetration on Concrete Structure can create corrosion on steel on reinforcement concrete. As we know today many people design concrete structure near the sea with the same like ordinary in high land. ACI and SNI actually have determined a concrete cover for concrete structure near the sea. This research aim to analyze chloride penetration according to concrete cover. Different concrete cover 20 mm, 40 mm, 60 mm and 70 mm are used in this research. Using finite element method show concrete cover is important thing to depend over corrosion and for life time of structure. These results also show ACI and SNI codes are right and must use over structure near the sea.